Faktor-Faktor Yang Mempengaruhi Keputusan Nasabah Dalam Pemilihan Kredit Kepemilikan Rumah (KPR) - Dimas Zaenal Arifin; Siti Aisyah; Retno Suwiyanti (ARBITRASE: Journal of Economics and Accounting, 2024)
The establishment of Islamic banks is one of the signs of the growth of the Indonesian banking industry. Sharia Home Ownership Credit (KPR) is a type of KPR that uses transactions in accordance with Islamic law. Clients who use the KPR financing facilities from Islamic banks will not experience fluctuating bank interest rates and uncertainty when obtaining home ownership credit. The purpose of this research is to determine the influence of factors such as religiosity, literacy, and costs on customers' decisions to use mortgage services at Islamic banks. This research is qualitative in nature, and the method used is a survey. Customers of Islamic banks who take out home purchase loans through the mortgage service in the Jabodetabek area are the respondents of this study. Using the non-probability sampling method, a questionnaire with a sample of one hundred people was distributed online to residents of Jabodetabek. The data analysis used is multiple linear regression analysis. Next, the data were collected with the help of SPSS Version 27. The test results show that the variables Religiosity (X1) and Literacy (X2) partially have a positive and significant impact on customers' decisions to choose mortgage services at Islamic banks (Y). Conversely, the variable Cost (X3) has a negative and significant impact on customers' decisions to choose mortgage services at Islamic banks. (Y).